Hajj pilgrims tracking and monitoring system - Mantoro, Teddy; Ayu, Media Anugerah, Md. Akhtaruzzaman; Mahmud, Murni (IIUM Press, 2011)

(untitled)
Hajj Pilgrim tracking system circumscribes three major areas from the user perspectives and accumulates together as an integrated and interactive monitoring system to apply in pervasive conglomerating environment during Hajj ritual. The Hajj is one of the most important activities and also one of the five pillars in Islam which is mandatory (if some important factors are fulfilled) for Muslims and has to perform at list one time in his or her life by visiting the Holy Ka'aba in Makkah with some holy activities. Missing pilgrims, locating lost, injury, health problem etc. are frequently encountered during Hajj that occurs sorrowfulness in their relatives' minds as well as the responsible committees. To reduce these problems and also to provide helps to the pilgrims, a new Hajj Pilgrim tracking system is proposed. Architectural and functional overview of the proposed monitoring and tracking system for Hajj Pilgrims are also presented in this chapter